Fight against fear : southern Jews and Black civil rights - Webb, Clive, 1970- (University of Georgia Press, 2001)
"In the uneasily shared history of Jews and blacks in America, the struggle for civil rights in the South may be the least understood episode. Fight against Fear is the first book to focus on Jews and African Americans in that remarkable place and time. Mindful of both communities' precarious and contradictory standings in the South, Clive Webb tells a complex story of resistance and complicity, conviction and apathy."--Jacket